An Evaluation of the Alteration in the Number of Neuron and Expression of S100B, MMP-9, and GFAP in Ischemic Rat Brain Tissue Induced by the Left Unilateral Common Carotid Artery Occlusion Method - Widayati, Aris; Rantam, Fedik Abdul; Machin, Abdulloh; Riawan, Wibi (Trends in Sciences, 2025)
Background: The middle cerebral artery occlusion (MCAO) model has been widely used as a tool for learning the focal ischemic stroke. However, the MCAO method has several limitations, including a lack of visibility and risk of subarachnoid hemorrhage. In addition, Common carotid artery (CCA) occlusion is another form of ischemic stroke type in human with a prevalence ranging from approximately 0.24 to 5 % among in ischemic stroke patients. Thus, CCA occlusion method can be developed as an alternative for creating ischemic stroke models to learn pathophysiology of ischemic stroke. Aim: The aim of this study is to prove whether an occlusion of the left CCA for 180 min in rat can induce ischemic stroke based on the change number of neuron and biomarker in brain tissue. Methods: The 15 male Wistar rats were randomly divided in to 3 groups. The first and second 5 rats, each of them were occluded on the left CCA for 60 and 180 min, then were categorized as the Group A and Group B respectively. Meanwhile, the remaining 5 rats without occlusion were included in the sham group. The assessment of the motoric dysfunction used LRWT tool to evaluate foot fault scoring (FFS) and foot placement accuracy, while the number and distribution of neuron was evaluated by H and E staining. The expression of MMP9 and S100B were assessed using Elisa technique, while GFAP was evaluated with immunohistochemistry technique. Results: The number of neuron in ischemic stroke groups (A and B) was significantly decreased compared to the sham group. Meanwhile, Expression of MMP9, S100B, GFAP was found to increase significantly in ischemic groups (A and B). Motoric function was found to decrease in ischemic stroke group (A and B) both in RHL and RFL. Conclusions: The occlusion of left unilateral CCA for 180 min yield in the declining number of the neurons, motoric deficit and in increasing of MMP9, S100B, GFAP expression. This finding was expected to give a new venue to develop preclinical research to learn pathophysiology of ischemic stroke. HIGHLIGHTS 180-min left CCA occlusion induces brain ischemia. Ladder Rung Walking Test confirms movement impairment in ischemic stroke. Neuron loss indicates stroke impact on brain tissue. Elevated MMP9, S100B, GFAP show neuroinflammation and astrocyte damage indicated brain damage. Findings support the use of this model for studying ischemic stroke pathophysiology. GRAPHICAL ABSTRACT